A Tremadocian (Early Ordovician) palaeoscolecidan worm from graptolitic shales in Hunan Province, South China. (18th November 2013) - Wang, Wenhui; Muir, Lucy A.; Botting, Joseph P.; Feng, Hongzhen; Servais, Thomas; Li, Lixia; Lane, Phil
Abstract A new locality exposing Tremadocian (Early Ordovician) graptolitic shales in Hunan Province, South China, has yielded an exceptionally well‐preserved annulated worm. This palaeoscolecidan is described as Waflascolex changdensis gen. et sp. nov. and reveals extremely fine detail of the cuticle organization and plating array. The new taxon is characterized by three critical characters: incomplete plate rows that occur only on the posterior end of the worm (except in the posterior‐most area) and do not extend over the entire circumference or along the entire trunk; a regular rhomboidal array of platelets around intercalations; and reduced cuticular organization at the posterior termination. The unique cuticular organization and platelet ornamentation in the new taxon offer insight into functional differentiation of plates in the scleritome. Palaeoscolecid distribution through the early Palaeozoic is reviewed, showing that the worms were widespread in the Cambrian and Ordovician, but became more restricted during the Silurian. Ordovician palaeoscolecidans are diverse in scleritome architecture, and strikingly different from Cambrian taxa, indicating that this group diversified as part of the Great Ordovician Biodiversification Event.